2002
DOI: 10.1097/00006231-200207000-00014
|View full text |Cite
|
Sign up to set email alerts
|

A class of asymmetrical nitrido 99mTc heterocomplexes as heart imaging agents with improved biological properties

Abstract: Asymmetrical heterocomplexes containing a terminal technetium-nitrogen multiple bond coordinated to one diphosphine ligand (PNP) and one dithiocarbamate ligand (DBODC), were obtained through a simple two-step procedure under controlled conditions. The resulting complexes [99mTc(N)(PNP)(DBODC)]+ are monocationic, and possess a distorted square-pyramidal geometry where the Tc triple bond N multiple bond occupies an apical position and the diphosphine and dithiocarbamate ligands span the residual four coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 4 publications
1
56
1
Order By: Relevance
“…Differences between the observed values of heart uptake reported here in female rats and previous data in the literature (2,3,18) could be attributed to differences in the composition of the injected solution. In particular, in our work we used a saline solution containing less than 5% (v/v) ethanol whereas other groups used a phosphate buffer solution (0.1 mol dm 21 ; pH 7.4) containing 10% (v/v) ethanol (2,3) or a saline solution containing 15% (w/w) propylene glycol (18).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Differences between the observed values of heart uptake reported here in female rats and previous data in the literature (2,3,18) could be attributed to differences in the composition of the injected solution. In particular, in our work we used a saline solution containing less than 5% (v/v) ethanol whereas other groups used a phosphate buffer solution (0.1 mol dm 21 ; pH 7.4) containing 10% (v/v) ethanol (2,3) or a saline solution containing 15% (w/w) propylene glycol (18).…”
Section: Discussioncontrasting
confidence: 87%
“…Previ ously, we reported a new class of nitrido 99m Tc agents of the type [ 99m Tc(N)(DTC)(PNP)] 1 , where DTC is a dithiocarbamate ligand and PNP an aminodiphosphine ligand, as potential myocardial imaging agents (1)(2)(3). Among the tested compounds, [ 99m Tc(N)(DBODC)(PNP5)] 1 and [ 99m Tc(N)(DBODC)(PNP3)] 1 ( Fig.…”
mentioning
confidence: 99%
“…The difference in the heart uptake of cationic 99m Tc radiotracers is most likely caused by their lipophilicity and capability to across the plasma and mitochondrial membranes. Cationic 99m Tc radiotracers with the log P>1.5 often have a low heart uptake and a slow liver clearance while more hydrophilic cationic radiotracers with log P<0 tend to show fast washout from the myocardium (1)(2)(3)(22)(23)(24)(25). In both cases, the heart/liver ratio is low because of either high liver uptake or fast myocardial washout.…”
Section: Discussionmentioning
confidence: 99%
“…However, a dramatic difference was observed in liver washout, which was remarkably rapid and quantitative. In particular, at 60 min after injection in rats, the heart-to-liver ratio of 99m Tc-N-DBODC was approximately 10 times higher than that of 99m Tcsestamibi and 99m Tc-tetrofosmin (2)(3)(4). On the basis of these promising results, this study was designed to evaluate the safety profile and the biodistribution of 99m Tc-N-DBODC in healthy human volunteers under both stress and rest conditions.…”
mentioning
confidence: 90%
“…1) was studied extensively in rats (3,4) and dogs (5) and compared with that of the commercial radiopharmaceuticals 99m Tc-sestamibi (Cardiolite; Bristol-Myers Squibb Medical Imaging, Inc.) and 99m Tctetrofosmin (Myoview; GE Healthcare). These results in animals showed that heart uptake of 99m Tc-N-DBODC and washout from blood and lungs, as well as kinetic behavior as determined in dogs, are similar to those of the other 2 cardiac agents (5).…”
mentioning
confidence: 99%